2010
DOI: 10.1021/jo100061s
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomerically Pure Polyheterocyclic Spiro-β-lactams from trans-4-Hydroxy-l-proline

Abstract: The "Staudinger ketene-imine reaction" between ketenes generated from natural O,N-protected trans-4-hydroxy-l-prolines and the N-benzyl-N-benzylideneamine led to mixtures of diastereoisomeric, enantiomerically pure pyrrolidine-derived spiro-beta-lactams with a relative cis configuration. These were transformed into the corresponding pyrroline-spiro-beta-lactams by means of treatment with a base and the new C=C double bond was submitted to a number of different reactions in order to evaluate its reactivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…48 The removal of the mesyloxy group from the pyrrolidine ring of spiroazetidinones 48 through elimination in a basic medium has been deployed to create a carbon-carbon double bond, resulting in a pyrroline ring system (Scheme 71). 30 Thus, treatment of N-Cbz-protected compounds 48a and 48b with potassium carbonate led to the formation of enantiomeric products 187a and 188, respectively. However, the corresponding N-Boc-protected pyrrolidine reported to give 2-azetidinones, spiro-fused to cyclopropanes.…”
Section: Reactivity Of Substituents Attached To the Ring Nitrogen Atommentioning
confidence: 99%
See 1 more Smart Citation
“…48 The removal of the mesyloxy group from the pyrrolidine ring of spiroazetidinones 48 through elimination in a basic medium has been deployed to create a carbon-carbon double bond, resulting in a pyrroline ring system (Scheme 71). 30 Thus, treatment of N-Cbz-protected compounds 48a and 48b with potassium carbonate led to the formation of enantiomeric products 187a and 188, respectively. However, the corresponding N-Boc-protected pyrrolidine reported to give 2-azetidinones, spiro-fused to cyclopropanes.…”
Section: Reactivity Of Substituents Attached To the Ring Nitrogen Atommentioning
confidence: 99%
“…29 The formation of these products was explained by attack on the less hindered side of the ketene carbonyl by the imine, either via the -or -face approach, followed by mixtures of diastereomeric, enantiomerically pure spiro-fused 2-azetidinones. 30 Gonzalez and coworkers performed molecular modelling calculations using ab initio methods on the spiroazetidinones synthesised from the reaction of the ketene derived from Nbenzyloxycarbonyl L-proline acid chloride with some imines. 31 These calculations predicted that these systems could adopt a -turn secondary structure in solution, with strong intramolecular hydrogen bonds stabilizing the U-turn conformation with a geometry that is very close to the ideal type II -turns.…”
Section: N-mentioning
confidence: 99%
“…Because of their conformational ambiguity and strained nature, the synthesis and biocatalytic resolution of spiro‐β‐lactams may be an interesting as well as challenging task. Reports revealed that this type of molecules exhibit interesting biological activities 55–58 . Additionally, stereoselective spiro‐ β ‐lactams may act as precursors of unnatural β ‐amino acids.…”
Section: Applicationsmentioning
confidence: 99%
“…199 trans-4-Hydroxy-L-proline 29, a non-proteinogenic amino acid naturally occurring in plants and animals, 198 is a major component of collagen and is also used as a chiral synthon. 200 Due to its natural occurrence in animal collagen, it is usually produced by acid hydrolysis. Since this method necessitates a complex process of purification and thereby produces high volumes of waste, a better process is desired.…”
Section: Nd Critical Remark: Enzyme Engineeringmentioning
confidence: 99%